Modeling electrical characteristics of thin-film field-effect transistors III. Normally-on devices - Stallinga, Peter (2015)
The thin-film field-effect-transistor model recently developed is applied to devices based on materials that already show current even without a bias present at the gate resulting in so-called normally-on transistors. These fall in three categories: (i) narrow-band-gap semiconductors, where the thermal energy is sufficient to excite carriers across the band-gap, here analyzed for unipolar and ambipolar materials, (ii) doped semiconductors, and (iii) metals. It is shown what the impact is on the IV and transfer curves. (C) 2008 Elsevier B.V. All rights reserved.